2015
DOI: 10.1177/0973258615614420
|View full text |Cite
|
Sign up to set email alerts
|

Humour 2.0: Styles and Types of Humour and Virality of Memes on Facebook

Abstract: This research analyzes the communication process of humorous memes in the most vibrant online phenomenon, Facebook. Through quantitative and qualitative content analysis of 1,000 memes shared on a Facebook page, this research tests the effect of various styles and types of humour on the virality of memes. Self-defeating is the most effective style of humour although it is not the most frequently used. By applying the typology used in the context of broadcast and print media, this study shows that although sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 34 publications
2
30
0
4
Order By: Relevance
“…This could be related to the denotation of imperative words like "stop" that sounds demanding and authoritative. Moreover, the researcher found similar pattern to what was found by Taecharungroj and Nueangjamnong (2015) in which memes with "self-defeating" messages were largely high in terms of iconicity. A clear example of this is shown in Figure 7, which shows how a person admitted his dislike of mathematics although not all may have heard of Justin Bieber's song of "What do you mean?"…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This could be related to the denotation of imperative words like "stop" that sounds demanding and authoritative. Moreover, the researcher found similar pattern to what was found by Taecharungroj and Nueangjamnong (2015) in which memes with "self-defeating" messages were largely high in terms of iconicity. A clear example of this is shown in Figure 7, which shows how a person admitted his dislike of mathematics although not all may have heard of Justin Bieber's song of "What do you mean?"…”
Section: Resultssupporting
confidence: 80%
“…Studies on the use of Internet memes have shown contradictory findings particularly on its corresponding impact in marketing. Taecharungroj and Nueangjamnong (2015) in their study on the communication process of 1,000 humorous memes on Facebook, tested the effect of various styles and types of humour in determining the virality of memes. Based on their findings, it was found that self-defeating style in which the creator of the meme explains his or her own situation in a negative way is the most effective style of humour in luring attention by garnering huge number of shares.…”
Section: Memes and The Internetmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta jocosa alusión finaliza en la despedida del mensaje siguiente a través de la frase "queda con Dios", que se asocia con el emoji de unas manos juntas orando (person with folded hands, U0001F64F), que analizaremos también en (20). Las risas que introduce Andrea en el turno siguiente demuestran que la broma ha sido reconocida y aceptada por el interlocutor, por lo que su finalidad afiliativa se ha cumplido (Taecharungroj y Nueangjamnong, 2015).…”
Section: Sustantivosunclassified
“…As dinâmicas de ação coletiva nas mídias sociais, contudo, embora se configurem a partir de técnicas retóricas (Huntington, 2016) -muitas vezes conjugadas ao humor (Taecharungroj;Nueangjamnong, 2015) -, são; extremamente dependentes da apropriação e do espalhamento da mensagem, de tal modo que, como um grito de guerra, o grau de sucesso ou insucesso de uma campanha baseada em uma hashtag política permanece como uma obra aberta e incompleta, à espera não apenas das massas que a entoarão mas do modo como o farão. Assim, utilizá-las como estratégia de propaganda política compreende em grande medida abrir mão do controle sobre os resultados da ação, o que, naturalmente, não é um efeito desejável para o comando de campanha (Stromer-Galley, 2013).…”
Section: Palavras-chaves: a Propaganda Política Em Múltiplas Epistemesunclassified